Migration and identities in the globalized world - Bauman, Zygmunt (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2011)
The article analyzes the changing patterns of global migration and its consequences regarding the identity processes. After highlighting the change caused by the passage from 'solid' to 'liquid' modernity, the author suggests that identity can be interpreted as a constant process of construction and renegotiation, in a dialectic and provisory search for freedom and security.Keywords: Identity; Migration; Globalization; DiasporasO artigo analisa a mudança nos padrões da migração global e suas consequências no que diz respeito aos processos de identidade. Depois de elucidar sobre as mudanças causadas pela passagem da modernidade ‘sólida’ para ‘liquida’, o autor sugere que identidade pode ser interpretada como um constante processo de construção e renegociação, numa provisória e dialética procura pela liberdade e segurança.Palavras-chave: Identidade; Migração; Globalização; Diásporas